The Effect of Emotional Intelligence competences and Transformational Leadership on Organizational Performance An Investigation Study at Al-Rafidain Bank - دحام, غني; عوده, بلال كامل (Journal of Economics and Administrative Sciences, 2012)
The research deal with three variables of exceptional importance to organization business firms. These variables are emotional intelligence, transformational leadership, and organizational performance. The aim of this research is to determine the effect of emotional intelligence and transformational leadership on organizational performance at the banking sector, which is represented by Al-Rafidain Bank. The problem of the research is expressed by many questions related with the nature of the interrelationships and effects among research’s variables. The researcher has depended upon the descriptions - analytical approach. on a random sample of (80 ) managers working at more than sixteen branches of Al-Rafidain Bank in Baghdad and governorates. A questionnaire is used as a key instrument for gathering data and information. Many statistical tools have used for treating data collected. The most prominent results of the research are the significant relationships existing between emotional intelligence abilities and transformational leadership as well as between emotional intelligence and organizational performance. As for the most prominent recommendations one was the need to be aware of the fact that the banks examined, Emotional intelligence is one of the crucial elements in shaping and building leader Transfer, which is one of the priorities of contemporary organizations.